Income and happiness in Afghanistan: Do insecurity and violence matter? - Mohammad H. Asadi; Mohammad Reza Farzanegan (Philipps-University Marburg, School of Business and Economics, 2023)
We examine the relationship between household income and happiness in Afghanistan and the moderating roles of fear of insecurity and experiencing violence. Our study is based on surveys conducted by the Asia Foundation from 2014 to 2021 across 34 provinces in Afghanistan. Employing fixed effects ordered logit regressions, our results reveal a positive association between income and happiness. Additionally, we find a negative association between fear of insecurity, experiencing violence, and happiness. Among individuals with higher incomes and a fear of insecurity, the probability of having a high level of happiness declines by about 2.4% points when compared to those without such fear. Furthermore, for individuals with higher incomes who have experienced violence, the probability of having a high level of happiness declines by about 3.8% points when compared to those who have not experienced violence. However, for individuals with low incomes, insecurity and violence do not significantly impact their predicated level of happiness. This result can be attributed to two main issues. First, in conflict-affected areas, high-income individuals not only encounter the inherent dangers of their environment and the constant threat of terrorism, but also face increased risk of asset loss and institutional mistrust due to rampant corruption. Second, fear of insecurity and experiencing violence are influenced by psychological factors and diminish the positive impact of higher income on happiness. The results are robust to the inclusion of other socio-economic and demographic characteristics of the respondents.
Keywords: D74; H56; I31; N35; O15; 330; Happiness; Life Satisfaction; Conflict; Violence; Afghanistan; Ordered logit; Survey